The medicated child [videorecording (DVD)] - Gaviria, Marcela; Lyman, Will, 1948- (Distributed by PBS Home Video, 2008)
In recent years, there's been a dramatic increase in the number of children being diagnosed with serious psychiatric disorders and prescribed medications that are just beginning to be tested in children. The drugs can cause serious side effects, and virtually nothing is known about their long-term impact. "It's really to some extent an experiment, trying medications in these children of this age," child psychiatrist Dr. Patrick Bacon tells FRONTLINE. "It's a gamble. And I tell parents there's no way to know what's going to work."